Urgensi Strategi Peningkatan Branding Usaha Mikro Kecil dan Menengah di Kelurahan Rempoa melalui Rebranding Desain Banner: Perspektif Teori Neoklasik - Muhammad Junaidi; Mayyada Alfi Nasywa; Haura Hafizhah Zalfa; Reza Kurniyawan; Naswa Ariandita; Levina Idelia; Elve Oktafiyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Over the past two decades, Indonesia’s economy has experienced complex dynamics, with Micro, Small, and Medium Enterprises (MSMEs) serving as the backbone of the national economy. However, amid the rapid pace of digitalization, many MSME actors still face significant challenges in adapting to modern technology and branding strategies. This research and community service activity aims to analyze the urgency of enhancing MSME branding strategies in Rempoa Village through digital literacy and banner design rebranding from the perspective of neoclassical economic theory. The method employed is a collaborative approach through the 2025 Community Service Program (KKN) Group 20 of South Tangerang, involving direct participation of MSME owners in the redesign process of their business banners. This approach focuses on improving digital literacy and implementing visual rebranding as forms of entrepreneurial innovation aligned with the principles of efficiency and human capital investment. The results indicate that improving digital literacy expands market access, increases efficiency, and strengthens entrepreneurs’ adaptability to changing consumer behavior, while banner design rebranding effectively creates product differentiation, enhances business image, and increases visual appeal—positively influencing sales and brand awareness. From a neoclassical perspective, these strategies reflect the application of economic rationality principles in achieving market equilibrium, while Schumpeter’s concept of creative destruction is evident through visual transformation that replaces outdated strategies with modern and innovative approaches. Overall, the collaboration between academics and MSME actors through this KKN program successfully generated tangible impacts in strengthening the local economy, where digital literacy and banner design rebranding serve as concrete steps toward sustainable economic development based on innovation, efficiency, and entrepreneurial independence.